Creation of Sexually Transmitted Diseases Education Program for Young Adults in Rural Cambodia - Joseph Kai Man Kam; Joseph Kai Man Kam; Lok Ki Wong; Kirsten Ching Wah Fu (Frontiers Media S.A., 2019)
Introduction: Globally, adolescents and young adults aged from 15 to 24 years accounted for 25% of the sexually active population. They also took up almost 50% of all newly acquired sexually transmitted diseases (STDs) worldwide. In developing countries/ regions, there have been more unreported cases due to the limited resources and availability of data. This project aimed to enhance sexual health knowledge and encourage behavioral change in sexual practice in rural Cambodia by educational interventions.Methods: A multi-prong project used the Theory of Planned Behavior (TPB) as framework to guide the implementation, which involved carrying out educational talks, group discussion sessions. The educational health talks described the signs and symptoms of STDs and preventive measures including the Abstinence-Be faithful- Condom (ABC) strategy. Pre- and post-intervention assessments were conducted on 111 villagers aged between 18 and 30 years who lived in Peaksneng Thyme Village, Cambodia. Special materials were prepared that highlighted such information were also given to all participants. This was followed by discussion sessions that aimed to strengthen an appropriate attitude toward STDs. A pilot trial was done to prepare and build a constructive, realistic atmosphere and facilitated in-depth spread of main messages. A 20-item assessment of STD knowledge was used as pre- and post-intervention evaluation tool. Individual participant scores were compared to determine the effectiveness of interventions.Conclusion: This comprehensive program was effective in enhancing sexual knowledge in high-risk groups of both sexes as well as general public in rural Cambodia. With experiences gained, this could be replicated in nearby communities, possibly motivating community behavioral change in future. Alternatively, this approach could be further developed, or using other behavioral theories, and applied to other health issues in this country.